PERBANDINGAN EFISIENSI DYE SENSITISIZED SOLAR CELL (DSSC) DARI EKSTRAK DAUN PACAR AIR, EKSTRAK BUNGA PACAR AIR MERAH DAN UNGU (IMPATIENS BALSAMINA LINN) SEBAGAI DYE SENSITIZER - Alimuddin, Arni; Iswadi, Iswadi; Sahara, Sahara (JFT : Jurnal Fisika dan Terapannya, 2016)
Research on Comparison Of Efficiency Dye Sensitized Solar Cell (Dssc) Of Henna Leaf Extract Water, Water Henna Flower Red And Purple (Impatiens Balsamina Linn) as a Dye Sensitizer in order to determine how much comparative efficiency of dye sensitisized solar cell (DSSC ) of water henna leaf extract, flower extract water henna red and purple as a dye sensitizer. The method used in this research is the method of Doctor Blade. Based on the results of measurements of I-V by using a source of light, the efficiency gained from henna leaf extract 0.008473333% water by absorption spectrum wavelengths are in the range of 245- 660.50 nm and an absorbance of 0.036. For efficient water henna red flowers of 0.007466667% of this extract is the wavelength range of 242.50 - 312 500 nm and absorbance of 4573, while for the water purple flowers girlfriend 0.004833333% efficiency results obtained in the wavelength range 238.50 - 350.50 nm and absorbance 4,617 , Henna leaf extract water as a dye sensitizer on sensitisized dye solar cell (DSSC) have the highest efficiency.